PENDIDIKAN KESEHATAN TENTANG PREMENSTRUAL SYNDROME (PMS) PADA REMAJA PUTRI DI WILAYAH KERJA BIDAN VERONICA - Gusti Maulani, Rici; Siagan, Devia Ester Leona (Awal Bros Journal of Community Development, 2022)
Premenstrual syndrome is a condition that describes a number of symptoms that occur regularly and are related to the menstrual cycle. Usually, these symptoms appear 7-10 days before menstruation and disappear when menstruation begins (El Manan, 2011). There are approximately 200 symptoms that appear with PMS but the most common symptoms are irritability and dysphoria (feeling sad). Symptoms of premenstrual syndrome include physical, emotional and behavioral symptoms. The etiology of premenstrual syndrome (PMS) is unclear, but perhaps one factor that plays an important role is the balance between estrogen and progesterone with consequent fluid and sodium retention, weight gain, and sometimes edema (Wiknjosastro, 2005). Premenstrual syndrome (PMS) is a symptom that appears as a result of hormonal changes that occur in a woman's body before menstruation. The results of research conducted by the American College of Obstetricians and Gynecologists (ACOG) in 2012, reported that PMS symptoms were experienced by about 65.7 adolescent girls. Based on research from the World Health Organization (WHO), it was found that the symptoms of PMS experienced by 23% of Indonesian women indicate that there are quite a number of PMS sufferers in Indonesia, so it is necessary to take countermeasures to prevent and overcome them.